KECENDERUNGAN KORELASI ANTARA POLA MAKAN DAN AKTIVITAS FISIK DENGAN DERAJAT HIPERTENSI PADA LANSIA - Arikhman, Nova (Jurnal Ipteks Terapan, 2012)
This research is to find out relationship of meal pattern and physical activity with the hypertension degree, in the work area of Kinali Public Health Center. The research is descriptive correlation by using cross-sectional approach. The research population are 192 elderly, who have hypertension and aged above or the same 55 years old. To collect data, the researcher uses questioners with guided interview and blood pressure measurement directly to have meal pattern and physical activity with hypertension degree. Based on the data analyses, it is found that elderly who are categorized as having less meal pattern are 53,1%, less physical activity are 51,5%. The statistical analysis, it is found that there is relationship of meal pattern and physical activity with the hypertension degree to elderly. On the based of the research findings, it is recommended that hoped to elderly and their family in order to keep adjusting their meal pattern and regular physical activity. Therefore, their blood pressure returns to normal and stable.